Mediating effects of work-family factors in the relationship between organizational characteristics and intention to stay. - Mustapha, Noraani; Ahmad, Aminah; Uli, Jegak; Idris, Khairuddin (Eurojournals, 2010)
Employee attrition has been a major concern among researchers in human resource development (HRD) area since it has negative impact on organization. This study was conducted to test the mediating effects of work-family facilitation and family satisfaction on the relationship between organizational characteristics as the independent variables and intention to stay as the dependent variable. By using self-administered research questionnaire, data was collected from 240 single mother employees age 45 and below and having at least one child. Samples were selected through simple random sampling method whereby six out of 24 single mother associations were selected to obtain research samples. Descriptive statistical analysis was conducted to describe the respondents. Pearson Product Moment Correlation was used to determine the relationships among variables and Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to verify the presence of mediation effects. Then the Soble’s z-test was used to test whether the mediators carry the effect of the independent variables on the dependent variable. The findings indicated that there were positive and negative significant relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize organizational factors along with work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees.